Mixed Conductive, Injectable, and Fluorescent Supramolecular Eutectogel Composites - Criado Gonzalez, Miryam (2023)
Eutectogels are an emerging family of soft ionic materials alternative to ionic liquid gels and organogels, offering fresh perspectives for designing functional dynamic platforms in water-free environments. Herein, the first example of mixed ionic and electronic conducting supramolecular eutectogel composites is reported. A fluorescent glutamic acid-derived low-molecular-weight gelator (LMWG) was found to self-assemble into nanofibrillar networks in deep eutectic solvents (DES)/poly(3,4-ethylenedioxythiophene) (PEDOT): chondroitin sulfate dispersions. These dynamic materials displayed excellent injectability and self-healing properties, high ionic conductivity (up to 10−2 S cm−1), good biocompatibility, and fluorescence imaging ability. This set of features turns the mixed conducting supramolecular eutectogels into promising adaptive materials for bioimaging and electrostimulation applications.